Offshore mariculture: Workboats - Beaz Paleo J.D.; Muir J.; Turner R. (Mediterranean offshore mariculture, 2000)
Offshore mariculture: Workboats#insystems. Based on careful assessment of site conditions, and an appreciation of cagesystem characteristics and farm operating requirments, suitable mooring specifications may be developed. This process isparticularly important for offshore mariculture, where environmental loading may befar more demanding. This paper reviews the engineering aspects of mooring marine aquclue systems with respect to potential site conditions.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)